Implementation of Proning Position to Reduce Dispnea in Asthma Patients - Dimas Anugra; Aris Hidayat (STIKES Hesti Wira Sriwijaya, 2025)
Introduction: Asthma is a chronic respiratory disease that is a serious public health problem in many countries worldwide. This disease disrupts daily life, impacting quality of life and productivity. Asthma sufferers generally experience muscle spasms that can cause shortness of breath, difficulty expiratory, decreased lung capacity, and physical weakness. To overcome shortness of breath, the prone position can be applied. The purpose of this study was to describe the application of the prone position in patients with bronchial asthma who have nursing problems related to ineffective breathing patterns. Method: The research used was quantitative. The research used a descriptive method with a case study approach. This was to explore the therapy of providing a prone position to reduce shortness of breath in patients. This case study was conducted in the emergency room of Dr. AK Gani Hospital, Palembang. This case study was conducted in May 2025. The subjects of this case study were two patients with bronchial asthma. Results: After applying the prone position to patient 1 and patient 2, both patients experienced an increase in oxygen saturation levels and a decrease in respiratory rate. Conclusion: Applying the prone position effective to increase oxygen saturation levels and reduce shortness of breath in patients with bronchial asthma.